Non-RBD peptides of SARS-CoV-2 spike protein exhibit immunodominance as they elicit both innate and adaptive immune responses - Deepika Rathore; Preeti Chauhan; Anvesh Bonagiri; Lekha Gandhi; Deepti Maisnam; Ramesh Kumar; Anupama T. Row; M.M. Kesavulu; Musturi Venkataramana (Heliyon)
Severe acute respiratory coronavirus-2 (SARS-CoV-2) emerged in 2019 as a new virus and caused worldwide outbreaks, quickly turning into a pandemic disease called coronavirus disease-19 (COVID-19). All the existing methodologies were used for developing vaccines for this virus. But sporadic infections of this virus and the emergence of new strains to date suggest the incomplete protection offered by the developed vaccines and the need for new research. In this direction, we identified five epitopes present in the non-RBD region and on the surface of the spike protein by in silico analysis. They are epitope I (aa 80–90), epitope II (aa 262–270), and a small protein with three epitopes (aa 1059–1124). Antigenicity scores of these epitopes were found to be higher than the full length spike protein and its RBD region. These epitopes showed high conserveness across the emerging strains, high immunogenicity, non-toxicity, no homology with human sequences and high affinity for MHC class I & II molecules. Antibodies raised against these epitopes interacted with the bacterially expressed spike protein in western blotting. The antiserum of COVID-19 recovered participants reacted with the developed epitopes (small protein). Furthermore, in the presence of the respective antiserum and COVID-19 convalescent serum, these epitopes successfully fixed the complement, implying a possible role in innate immunity. The epitopes were also found to activate the peripheral blood mononuclear cells (PBMCs) isolated from the blood samples of COVID-19 recovered/vaccinated participants, suggesting a possible role in adaptive immunity. The need for the new SARS-CoV-2 vaccines is further highlighted in light of current reports about the side effects of a developed vaccine (AstraZeneca) and the circulating new strains. The epitopes presented in this study represent the potential immunogens and expect certain pitfalls of the existing vaccines would be sealed.